Laparoscopic Versus Open Major Hepatectomy for Hepatocellular Carcinoma: A Meta-Analysis. Issue 5 (October 2018) - Chen, Ke; Pan, Yu; Hu, Geng-yuan; Maher, Hendi; Zheng, Xue-yong; Yan, Jia-fei
Abstract : Background: Although large series of laparoscopic resections for hepatocellular carcinoma (HCC) were published, reports of laparoscopic major hepatectomy (LMH) are still limited in expert centers because LMH for HCC remains a challenging procedure requiring extensive experience in both laparoscopic and hepatic surgery. We performed a meta-analysis to assess the safety and efficacy of LMH and open major hepatectomy (OMH) for HCC. Methods: A literature search was performed to identify studies comparing LMH with OMH for HCC. Postoperative morbidity, mortality, operative time, intraoperative blood loss, length of hospital stay, R0 rate, and long-term survival outcomes were analyzed. Results: Eight studies with a total of 780 HCC patients were included for meta-analysis. The pooled data showed that LMH was associated with longer operative time [weighted mean differences (WMD)=81.04 min; 95% confidence interval (CI), 37.95 124.13; P <0.01], less blood loss (WMD=−117.14 mL; 95% CI, −170.35 −63.93; P <0.01), and shorter hospital stay (WMD=−3.41 d; 95% CI, −4.90 −1.92; P <0.01). Overall morbidity was significantly lower in the LMH group (odds ratio=0.45; 95% CI, 0.23 0.86; P =0.02), as were major complications (odds ratio=0.36; 95% CI, 0.18 0.73; P <0.01). However, there was no difference in margin negativity and long-term survival outcomes. Conclusions: LMH can be performed as safely and efficiently as OMH for HCC regarding both surgical and oncological outcomes. LMH is associated with less intraoperative blood loss and postoperative morbidity and may serve as a promising alternative to OMH for HCC patients.